2003
DOI: 10.1002/chin.200306022
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Catalytic Asymmetric Addition of Alkyl Groups to Ketones.

Abstract: Enantioselective syntheses Enantioselective syntheses O 0031A Practical Catalytic Asymmetric Addition of Alkyl Groups to Ketones. -The camphor derivative shown in the scheme is an efficient ligand for asymmetric addition of alkyl groups to ketones. Tertiary alcohols are obtained with excellent enantioselectivity. -(GARCIA, C.; LAROCHELLE, L. K.; WALSH*, P. J.; J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…2b) [24,25]. In addition, diarylzinc reagents as well as a,b-unsaturated ketones were successfully employed using this ligand.…”
Section: Discussionmentioning
confidence: 99%
“…2b) [24,25]. In addition, diarylzinc reagents as well as a,b-unsaturated ketones were successfully employed using this ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The data show that both the catalytic activities and enantioselectivities of (S)-NOBIN derived ligands (2,4,6,8) were generally better than those of the corresponding (R)-NOBIN derivatives (1,3,5,7), which should be attributed to the different chiral matching effects of (R)-NOBIN and (S)-NOBIN's binaphthyl skeleton with (S)camphor's isoborneol backbone. Furthermore, the single sulfonyl derivatives of (S)-NOBIN (4, 8) gave better enanotioselectivities than double sulfonyl derivatives (2,6), which indicated that NOBIN's hydroxyl group improves the performance of the ligands both on the conversion of benzaldehyde and the ee value of the addition product. Compared with ketocamphorsulfonylated NOBIN ligand 4, the corresponding hydroxycamphorsulfonylated NOBIN ligand 8 gave better enantioselectivity and offered the addition product with opposite configuration possibly because of the use of different spatial arrangement of the complex catalyst.…”
Section: Catalytic Asymmetric Alkylation Of Aldehyde With Dialkylzincmentioning
confidence: 92%
“…Since Ramón and Yus firstly reported several camphorsulfonamide ligands promoting addition of dialkylzincs to aldehydes and ketones in the presence of titanium alkoxide, many camphorsulfonamide ligands derived from various aliphatic and aromatic monoamines and diamines have been tested in the addition of dialkylzinc reagents to carbonyl groups with varying success in the presence of titanium alkoxide . Among these ligands, Walsh's HOCSAC, a bis (hydroxycamphorsulfonamide) ligand derived from ( R , R )‐1,2‐cyclohexyl diamine, has been shown to be the best one so far to give excellent results with up to 99% ee value using only 2% catalyst loading.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The design of catalysts for the asymmetric additions of organozinc reagents to aldehydes and ketones to give chiral alcohols has been the focus of intensive research and a large number of diverse catalysts have been developed. [10][11][12][13][14][15][16][17][18][19] Naturally occurring cinchona alkaloids and their derivatives have been widely used in a variety of asymmetric reactions with high catalytic efficiencies, [20][21][22][23][24][25][26][27][28] but they are less efficient [29][30][31][32] in the asymmetric organozinc addition reactions compared to other chiral ligands such as Walsh's HOCSAC [33][34][35][36][37][38][39] (a bis (hydroxycamphorsulfonamide) ligand derived from (R, R)-1,2-cyclohexyl diamine) and DAIB [40][41][42][43][44][45] (3-exo-dimethylaminoisoborneol). Herein, we report the development of a highly efficient trifunctional chiral phosphoramide-Zn(II) complex which can activate the asymmetric additions of diethylzinc with aldehydes to give desired alcohol products with excellent yields and enantiomeric excess (ee) values up...…”
Section: Introductionmentioning
confidence: 99%